2002
DOI: 10.1097/00003246-200204000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of posttreatment with propofol on mortality and cytokine responses to endotoxin-induced shock in rats*

Abstract: The early posttreatment of propofol after endotoxin injection drastically reduced the mortality rate of rats and attenuated their cytokine responses. Moreover, propofol attenuated the production of tumor necrosis factor-alpha. These findings suggest that propofol administration may be beneficial during sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 10 publications
4
48
3
1
Order By: Relevance
“…The increase in TNF-α may be an adaptive response of a jeopardized myocardium [18] . Low-and high-dose propofol (1 and 10 mg·kg -1 ·h -1 , respectively) exert beneficial effects on septic shock in rats and reduce serum TNF-α and IL-10 production after sepsis [19] . The difference between the results obtained here and these previous reports may be due to the administration of a long-term high-dose propofol infusion in this study; the use of high doses of propofol for prolonged periods is generally linked to a decrease in performance [3,15,17] .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in TNF-α may be an adaptive response of a jeopardized myocardium [18] . Low-and high-dose propofol (1 and 10 mg·kg -1 ·h -1 , respectively) exert beneficial effects on septic shock in rats and reduce serum TNF-α and IL-10 production after sepsis [19] . The difference between the results obtained here and these previous reports may be due to the administration of a long-term high-dose propofol infusion in this study; the use of high doses of propofol for prolonged periods is generally linked to a decrease in performance [3,15,17] .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our study shows, for the first time, that, at therapeutic concentrations, propofol inhibits the respiratory burst, degranulation, and chemotaxis of fMLF-activated neutrophils by competitively binding to FPR1 and thus attenuating downstream signaling, including in the Ca 2+ , AKT, and ERK1/2 pathways. There is considerable evidence from clinical and experimental studies that propofol exerts significant protective effects against inflammatory and cardiovascular diseases, inhibiting the production of cytokines and the clearance of ROS (3,30). Propofol has been shown to reduce oxidative injury to organ in endotoxemia animals (31) and in patients undergoing cardiac surgery (32).…”
Section: Discussionmentioning
confidence: 99%
“…As well as its anesthetic effects, there is growing evidence in animal and human studies that propofol exerts protective effects during acute inflammatory processes (1). In animal studies, propofol has decreased cytokine release during sepsis (2,3) and reduced neutrophil-mediated inflammation in acute pulmonary injury (4,5). In human studies, propofol has attenuated myocardial reperfusion injury and pulmonary dysfunction following cardiopulmonary bypass by reducing free radical release and modulating the inflammatory process (6,7).…”
mentioning
confidence: 99%
“…In recent years, the antiinflammatory effects of propofol have been demonstrated in vitro and in vivo [10][11][12]. It is reported that after endotoxin injection, propofol treatment may reduce the production of inflammatory cytokines and the mortality rate in rats experiencing endotoxic shock [13]. Also, our previous work has shown that propofol can protect endothelial cells against lipopolysaccharide (LPS)-induced barrier dysfunction [14].…”
Section: Introductionmentioning
confidence: 99%